The codes of the global in the twenty-first century - Guasch, Anna Maria (Col·lecció AGI (Art, Globalisation, Identity), 2018)
At the start of the twenty-first century, the contemporary implies a clear desire to affirm a type of art that is expanding across the globe, challenging old geographical borders, and reclaiming narratives of place and displacement; in other words, new cultural practices that transfigure the relationship between the global and the local, and articulate the discourse of difference. Being in the place of here and now, working with others in simultaneous and specific practice, and contemplating the production of work in the experience of connection means raising the value of the performative aspect of practice and displacing the reflective role of cultural production. In the new cartography of this multifarious global art, the author, who combines theoretical and curatorial discourse with creative practice, defines how global concepts circulate from the critical analysis of transnational contemporary art to the global.